The Modulatory Role of Vitamin C in Boldenone Undecylenate Induced Testicular Oxidative Damage and Androgen Receptor Dysregulation in Adult Male Rats - Amany Behairy; Nabela I. El-Sharkawy; Taghred M. Saber; Mohamed Mohamed Soliman; Mohamed M.M. Metwally; Ghada I. Abd El-Rahman; Yasmina M. Abd-Elhakim; Maha M. El Deib (MDPI AG, 2020)
Background: This study explored the effect of vitamin C (Vit-C) administration on the reproductive function of adult male Wistar rats injected with boldenone undecylenate (BOL). Methods: Rats were randomly assigned into control, vehicle control, Vit-C (120 mg/kg b.wt./day, orally), BOL (received 5 mg/kg b.wt./week, IM) and BOL+Vit-C-treated groups. After eight weeks, hormonal assay, semen evaluation, testicular enzymes, and antioxidants biomarkers were assessed. Besides, the histopathological and immunohistochemical investigations of the androgen receptor (AR) expression were performed. Results: The results revealed that serum testosterone, acid phosphatase, sorbitol dehydrogenase, sperm abnormalities, and testicular malondialdehyde were significantly incremented in the BOL-treated group. Testicular weight, sperm count, and sperm motility together with serum levels of luteinizing hormone, follicle-stimulating hormone, and estradiol, and testicular testosterone, catalase, superoxide dismutase, and reduced glutathione showed a significant decrease following BOL treatment. Besides, the AR immunoreactivity was significantly decreased in testicular tissues. Vit-C co-administration with BOL significantly relieved the BOL-induced sperm abnormalities, reduced sperm motility, testicular enzyme leakage, and oxidative damage. However, Vit-C could rescue neither BOL-induced hormonal disturbances nor AR down-regulation. Conclusions: The results provide further insight into the mechanisms of BOL-induced reproductive dysfunction and its partial recovery by Vit-C.